Screening and evaluation of anticancer property in mango fruit mangifera indica - Amid, Azura; Jaswir, Irwandi; Othman, Muhd Ezza Faiez (IIUM Press, 2011)
Cancer is a disease which known throughout the world. There are many available commercial and alternative treatments to treat cancer. Mango (Mangi(era indica L) is one the popular tropical fruits found in Malaysia. Mango is a wide variety that can easily be found in this country. It is known for its vibrant flesh colour, juicy texture, sweet flavour, vitamins and minerals. This study aimed to evaluate the anticancer property of mango variety that available in Malaysia (Siamese, Honey, Kuinin and Chokonan) towards human breast cancer cell (MCF-7). Based on the result. it turned out that Kuinin has the lowest ICso value. 300 llgmL-1 compared to other mango variety. suggesting that Kuinin as fruit has potential in preventing breast cancer.